2015
DOI: 10.4028/www.scientific.net/ssp.226.87
|View full text |Cite
|
Sign up to set email alerts
|

Cracking of 7CrMoVTiB10-10 (T24) Steel Weld Joints

Abstract: 7CrMoVTiB10-10 (T24) steel was designed for high temperature applications, especially for water wall panels in modern supercritical coal-fired boilers. However, welding of T24 steel caused many problems due to its cracking susceptibility. In the present paper the causes of T24 steel weld joints cracking have been discussed. Microstructural and fractographic analysis of weld joint were conducted and hardness was measured. It was found that the main causes of crack’s formation in weld metal are hot cracking susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Steel 7CrMoVTiB10-10 was launched on the market (and used primarily in the production of waterwalls) as a result of power engineering development, to address issues related to the retrofit of power generation equipment necessitated by an increase in generated power as well as to improve mechanical properties and eliminate the necessity of heat treatment. The steel was obtained through the modification of the chemical composition of steel 10CrMo9-10 (T22), involving the addition of microagents including vanadium, titanium, boron and nitrogen [1,3,4,6,7]. Assumedly, a decreased carbon content in the steel should translate into significantly better weldability and lower hardness, whereas the presence of microagents such as boron, titanium and vanadium should improve creep strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steel 7CrMoVTiB10-10 was launched on the market (and used primarily in the production of waterwalls) as a result of power engineering development, to address issues related to the retrofit of power generation equipment necessitated by an increase in generated power as well as to improve mechanical properties and eliminate the necessity of heat treatment. The steel was obtained through the modification of the chemical composition of steel 10CrMo9-10 (T22), involving the addition of microagents including vanadium, titanium, boron and nitrogen [1,3,4,6,7]. Assumedly, a decreased carbon content in the steel should translate into significantly better weldability and lower hardness, whereas the presence of microagents such as boron, titanium and vanadium should improve creep strength.…”
Section: Introductionmentioning
confidence: 99%
“…Welds made in the steel contained numerous hot, cold and relaxation cracks. Such a situation could be ascribed to the presence of numerous welding imperfections (of acceptable size), subsequently leading to the propagation of cracks as well as to the negative effect of secondary hardness resulting from the steel composition, the wide range of brittleness temperature, significant deformations of welds as well as the negative effect of hydrogen, present both during the process of welding and during the operation of welded structures [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…below 10 mm [7]. Industrial practice showed that welded joints of T24 steel are low ductility [11][12][13][14] and susceptible to cracking [15][16][17], especially cracks in the root pass in butt welded joints of tubes or pipes [18][19][20][21]. Examples of such macro-cracks in the root pass are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of the chemical composition and of the heat treatment of the above-named steel in relation to steel 10CrMo9-10, constituting the design basis for the new grade, led to the obtainment of higher mechanical properties at the cost of weldability. Experience related to the fabrication and operation of tight walls provide information about the high susceptibility of steel 7CrMoVTiB10-10 to cracking, which was described in detail in related reference publications [15][16][17][18][19][20][21][22][23][24][25]. …”
Section: Introductionmentioning
confidence: 99%